Size-effect of Kondo scattering by Fe impurities in Cu point contacts - Van der Post, N.; Mettes, F.; Mydoch, J.A.; Ruitenbeek, J.M.van; Yanson, I.K. (Физика низких температур, 1996)
The low temperature dVldl(V) characteristics are investigated for point contacts of various sizes (d ≈ 2-35 nm) using a mechanically controlled breakjunction of a Kondo alloy CuFe (0.1 at. %). A size effect, being manifested in an increase in the effective Kondo temperature with decreasing contact size, is found both on voltage and magnetic field dV/dl dependences. In accordance with the prediction of the Zarand-Udvardi theory the enhancement of the Kondo temperature in the CuFe alloy appears to be quantitatively much smaller than in CuMn alloy of the same concentration. This enhancement is due to the strong fluctuations of the local electron density of states in the ultrasmall metallic contacts. The Kondo temperature of a magnetic impurity provides a local probe of these fluctuations.